The effects of plyometric exercise on unilateral balance performance - Twist, C.; Gleeson, N.; Eston, R. (Journal of Sports Sciences, 2008)
The purpose of this study was to determine the effects of plyometric exercise on unilateral balance performance. Nine healthy adults performed baseline measurements on the dominant limb that consisted of: a 20-s unilateral stability test on a tilt balance board, where a higher stability index represented deterioration in balance performance; isokinetic plantar flexion torque at 0.52 and 3.14 rad · s-1; muscle soreness in the calf region; and resting plantar flexion angle. Plyometric exercise consisted of 200 counter-movement jumps designed to elicit symptoms of muscle damage, after which baseline measurements were repeated at 30 min, 24, 48, and 72 h. Perceived muscle soreness of the calf region increased significantly following the plyometric exercise protocol (F4,32 = 17.24, P < 0.01). Peak torque was significantly reduced after the plyometric exercise protocol (F4,32 = 7.49, P < 0.05), with greater loss of force at the lower angular velocity (F4,32 = 3.46, P < 0.05), while resting plantar flexion angle was not significantly altered compared with baseline values (P > 0.05). The stability index was significantly increased (F4,32 = 3.10, P < 0.05) above baseline (mean 2.3, s = 0.3) at 24 h (3.3, s = 0.4), after which values recovered. These results indicate that there is a latent impairment of balance performance following a bout of plyometric exercise, which has implications for both the use of skill-based activities and for increased injury risk following high-intensity plyometric training.